2020
DOI: 10.21315/tlsr2020.31.1.6
|View full text |Cite
|
Sign up to set email alerts
|

First Records of Morphological Diversity and Ecology of Periphytic Cyanobacteria from Tukun River, Penang Forest Reserve, Malaysia

Abstract: Despite the abundance of streams and rivers in Malaysia, the algal communities of these lotic ecosystems have remained largely unstudied. In a one-year floristic survey conducted from December 2014, 24 cyanobacterial morphospecies were identified for the first time from Tukun River, Penang Forest Reserve. Ten morphospecies were identified directly from field specimens while the remaining 14 morphospecies were identified only in cultures derived from the field samples. A total of 17 morphospecies; Leptolyngbya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
3
Order By: Relevance
“…була знайдена лише в донних відкладах річок Ейр-Терджун та Ейр-Ітам. Кілька видів Scytonema зареєстровані у верхніх частинах р. Тукун в Малайзії, колонізуючи різні типи субстратів (Azizan et al, 2020). За даними літератури (Paerl et al, 2000), види Scytonema поширені в усьому світі, включаючи донні відклади прісних вод у тропіках.…”
Section: результати та обговоренняunclassified
See 2 more Smart Citations
“…була знайдена лише в донних відкладах річок Ейр-Терджун та Ейр-Ітам. Кілька видів Scytonema зареєстровані у верхніх частинах р. Тукун в Малайзії, колонізуючи різні типи субстратів (Azizan et al, 2020). За даними літератури (Paerl et al, 2000), види Scytonema поширені в усьому світі, включаючи донні відклади прісних вод у тропіках.…”
Section: результати та обговоренняunclassified
“…Види Scytonema містять гетероцисти (або гетероцити), що здійснюють азотфіксацію. Їхня поява може бути показником зниження рівня азоту в навколишньому середовищі (Azizan et al, 2020). Можна припустити, що представники Scytonema вимагають низького рівня концентрації поживних речовин і не можуть існувати в органічно забруднених водах.…”
Section: результати та обговоренняunclassified
See 1 more Smart Citation
“…Studies on the ecology and diversity of mangrove cyanobacteria have been conducted in several regions, including India [24][25][26][27], Brazil [28][29][30], Tanzania [31], and Saudi Arabia [32]; however, research on cyanobacterial diversity in Malaysia has only been conducted in freshwater ecosystem and aquaculture ponds, with identification only to genus level [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In associations, they live within some tissues of the associative organism (endophytic) or in the surroundings (epiphytic association) (Andrews, Harris 2000;Azevedo 1998). In epiphytic associations, cyanobacteria form the periphyton with phytoplanktonic algae (Azizan et al 2020), and with aquatic macrophytes (Pimenta 2020), and this periphytonmacrophyte association is described as an ecological unit in aquatic ecosystems (Azim, Asaeda 2005;Camargo, Ferragut 2014). In this study, we found homocytous and heterocytous filamentous strains of epiphytic cyanobacteria associated with submerged leaves of the aquatic fern Salvinia auriculata, a macrophyte that performs important ecological roles (Julien, Center, Tipping 2002;Julien et al 2009;Room 1983).…”
Section: Introductionmentioning
confidence: 99%